Government Provisions Regarding Voting Rights in General Elections - Hidayani, Sri; Mina, Revi Fauzi Putra (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2022)
This research aims to analyze government provisions that affect voting rights in general elections. The main focus of the research is to explore how government policies and regulations can affect the exercise of voting rights and their impact on integrity and participation in the democratization process. The research methodology used a mixed approach combining legal document analysis, interviews with relevant stakeholders, and a survey of voters. The research identified a number of factors that affect voting rights, including voter registration regulations, accessibility of polling stations, and transparency of the electoral process. The analysis also covered aspects of security and voter protection in order to assess the extent to which the government has effectively guaranteed voting rights. The research findings highlight challenges in the implementation of these provisions, such as lack of resources, abuse of power, and lack of public understanding of their voting rights. The implication of this research is the importance of responsive and transparent governance in creating an enabling environment for fair and inclusive voting rights. The results also provide a foundation for developing policy recommendations that can improve electoral integrity and increase public participation. By understanding these dynamics, it is hoped that governments can optimize their role in ensuring that voting rights as a key pillar of democracy are maintained.